Bridging Expository Literacy: The Effectiveness of the SQ4R Method Based on Local Wisdom SDGs in Overcoming Deficits in Understanding among Elementary School Students - Mita Sukma Nurjanah; Intan Budi komara; Rina Heryani (Universitas Pendidikan Ganesha, 2026)
This study is motivated by the low level of literacy skills among elementary school students in expository texts, as reflected in their weak reading comprehension abilities. This issue indicates a gap that needs to be addressed to support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4 on quality education. This study aims to analyze and examine the effectiveness of the SQ4R (Survey, Question, Read, Recite, Reflect, Review) method integrated with SDGs-based local wisdom values in improving students’ reading comprehension and expository writing skills. This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The subjects of the study were fifth-grade elementary school students divided into an experimental group and a control group. Data were collected through reading comprehension and expository writing tests using test instruments and were analyzed using descriptive and inferential statistics through a t-test. The results show a significant improvement in the experimental group compared to the control group. The integration of local wisdom values within the SQ4R stages enhances the relevance of learning and helps students better understand and reflect on information. Therefore, the SQ4R method based on SDGs-oriented local wisdom is effective as an innovative instructional strategy to improve students’ literacy and support meaningful and sustainable learning in elementary education, and can be utilized as an alternative instructional model for teachers to enhance the quality of literacy instruction.